Theoretical study of phase behaviour of DLVO model for lysozyme and γ-crystalline aqueous electrolyte solutions - Melnyk, R. (Condensed Matter Physics, 2015)
Mean spherical approximation (MSA), second-order Barker-Henderson (BH) perturbation theory and thermodynamic perturbation theory (TPT) for associating fluids in combination with BH perturbation theory are applied to the study of the structural properties and phase behaviour of the Derjaguin-Landau-Verwey-Overbeek (DLVO) model of lysozyme and γ-cristalline aqueous electrolyte solutions. Predictions of the MSA for the structure factors are in good agreement with the corresponding computer simulation predictions. The agreement between theoretical results for the liquid-gas phase diagram and the corresponding results of the experiment and computer simulation is less satisfactory, with predictions of the combined BH-TPT approach being the most accurate.